The response of cementoblasts to calcium phosphate resin–based and calcium silicate–based commercial sealers. (24th September 2012) - Hakki, S. S.; Bozkurt, B. S.; Ozcopur, B.; Gandolfi, M. G.; Prati, C.; Belli, S.
Abstract Aim To investigate cell viability and gene expression of cementoblasts (OCCM.30) exposed to extractable components released by resin‐based sealers with different chemical composition Hybrid Root Seal (HRS), SimpliSeal (SS), Real Seal (RS) and AH Plus (AH) and by a MTA‐based sealers Tech Biosealer Endo (TBE). Methodology Discs of all materials were prepared and allowed to set in humid conditions at 37° for 48 h. The discs were then incubated for 72 h at 37 °C to obtain material extracts (1/1) in DMEM. The extracts containing the components released by the sealers were filtered and other dilutions (1/2, 1/4) were prepared from the original solution (1/1). Original and diluted solutions were tested on the cementoblasts. Impedance‐based real‐time cell analysis (RTCA) was used to evaluate cell viability, quantitative real‐time polymerase chain reaction (QRT‐PCR) was used to examine the expression of mineralization‐related genes (osteocalcin; OCN, Runt‐related transcription factor‐2; Runx2, collagen type 1; COL I, alkaline phosphatase; ALP). For statistical analysis, one‐way analysis of variance (anova) and Tukey's honestly significant difference (HSD) tests were used. Results TBE (1/2), RS (1/2, 1/4), and HRS (1/2, 1/4) significantly decreased cell viability (P < 0.001). AH (1/2, 1/4) and SS (1/2, 1/4) had similar cell viability to the control at 30 h. All tested materials significantly decreased cell viability when compared to the control group except AH (1/2, 1/4) and SS (1/4) at 90 h. All of the tested sealers reduced COL I mRNA expressions when compared to the control. SS was associated with significant increases in OCN and Runx2 mRNA expressions when compared to the control (P < 0.001). Whereas all of the dilutions of TBE, RS and HRS significantly decreased BSP mRNA expressions (P < 0, 001), 1/2 and 1/4 dilutions of SS increased BSP mRNA expression (P < 0, 001). Except the 1/4 dilutions of AH and SS, all the sealer dilutions significantly reduced ALP mRNA expression in cementoblasts (P < 0, 001). Conclusions SimpliSeal and AH Plus resulted in more favourable response to cementoblasts because of their regulation potential on the mineralized tissue‐associated protein's mRNA expressions.